Sen and the Human Rights: Freedom as Material Object of Human Rights - Ibáñez, Eduardo (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
Specifically we understand that the capability approach of Amartya Sen, is his greatest contribution to thinking about human rights. In this paper, in addition to placing its origin and significance for them, we will put in relation the capability approach with some contributions of liberation thought on Latin American as Ellacuría, highlighting its importance in connection with an intercultural vision human rights. We will discuss other relevant versions of the capability approach, specifically that of Martha Nussbaum. Finally, the most relevant reviews are located and the author’s response to them.